2018
DOI: 10.1002/mc.22844
|View full text |Cite
|
Sign up to set email alerts
|

AKR1B10 activates diacylglycerol (DAG) second messenger in breast cancer cells

Abstract: Aldo-keto reductase 1B10 (AKR1B10) is upregulated in breast cancer and promotes tumor growth and metastasis. However, little is known of the molecular mechanisms of action. Herein we report that AKR1B10 activates lipid second messengers to stimulate cell proliferation. Our data showed that ectopic expression of AKR1B10 in breast cancer cells MCF-7 promoted lipogenesis and enhanced levels of lipid second messengers, including phosphatidylinositol bisphosphate (PIP2), diacylglycerol (DAG), and inositol triphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 42 publications
(98 reference statements)
0
38
1
Order By: Relevance
“…(42)(43)(44) In lung cancer, AKR1B10 is up-regulated in non-small cell lung carcinoma in smokers, (42) and in breast cancer, AKR1B10 promotes cancer growth and progression by promoting lipogenesis and lipid messenger-mediated signaling cascades and thus is a potential therapeutic target. (43,45) In conclusion, our study demonstrates that serum AKR1B10 can differentiate HCC from HCs, BLTs, and high-HCC-risk chronic hepatitis and cirrhosis with high accuracy. AKR1B10 also has privilege in detection of early-stage HCC and AFP-negative HCC.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…(42)(43)(44) In lung cancer, AKR1B10 is up-regulated in non-small cell lung carcinoma in smokers, (42) and in breast cancer, AKR1B10 promotes cancer growth and progression by promoting lipogenesis and lipid messenger-mediated signaling cascades and thus is a potential therapeutic target. (43,45) In conclusion, our study demonstrates that serum AKR1B10 can differentiate HCC from HCs, BLTs, and high-HCC-risk chronic hepatitis and cirrhosis with high accuracy. AKR1B10 also has privilege in detection of early-stage HCC and AFP-negative HCC.…”
Section: Discussionmentioning
confidence: 58%
“…AKR1B10 expression and potential as a biomarker is also reported in other tumors, such as lung, breast, and pancreatic cancers . In lung cancer, AKR1B10 is up‐regulated in non–small cell lung carcinoma in smokers, and in breast cancer, AKR1B10 promotes cancer growth and progression by promoting lipogenesis and lipid messenger‐mediated signaling cascades and thus is a potential therapeutic target …”
Section: Discussionmentioning
confidence: 85%
“…For example, cPLA2α has been shown to mediate EMT via the PI3K/AKT pathway [29]. Previous studies suggest that PIP 2 is upregulated in BC cells in which AKR1B10 is overexpressed [6], which prompted us to investigate the phosphatidylinositol and PI3K/AKT pathway in detail. Consistently, our study demonstrated that the PI3K/AKT pathway was up-regulated in AKR1B10-induced BC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, AKR1B10 has been reported to regulate phosphatidylinositol (3, 4)-bisphosphate (PIP 2 ) expression in BC cells [6]. PIP 2 is the substrate of phosphatidylinositol 3-kinase (PI3K) [16].…”
Section: Akr1b10 Activates Pi3k/akt Pathwaymentioning
confidence: 99%
See 1 more Smart Citation